2021
DOI: 10.3390/ijerph18105373
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internalized Stigma on LGBT Parenting and the Importance of Health Care Structures: A Qualitative Study

Abstract: Research on LGBTIQ+ families has focused on the effects of being in a diverse family on the development of children. We seek to show the experience of parenthood from the perspective of LGBTIQ+ people, considering its particularities and the role that health care services play as a potential support network. We used the biographical method through open-ended interviews, participants were LGBT people, and key informants from Chile, Colombia, and Mexico were selected based on a sociostructural sampling. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(45 reference statements)
0
4
0
2
Order By: Relevance
“…The majority (74%–79%) of Americans perceived that LGBT individuals face some discrimination in the United States today according to a poll by Kaiser Family Foundation in 2020 (Kirzinger et al, 2020). Discrimination is experienced by sexual and gender minorities not only in society, but also within the health care system (Alday-Mondaca & Lay-Lisboa, 2021; Ayhan et al, 2020). Health care providers including physicians (Prairie et al, 2018; Sabin et al, 2015), nurses (Englund et al, 2020; Grudzinski, 2019; Prairie et al, 2018; Stewart & O’Reilly, 2017), and mental health providers (Sabin et al, 2015) contribute to these discriminatory environments and experiences whether consciously or unconsciously.…”
Section: Introductionmentioning
confidence: 99%
“…The majority (74%–79%) of Americans perceived that LGBT individuals face some discrimination in the United States today according to a poll by Kaiser Family Foundation in 2020 (Kirzinger et al, 2020). Discrimination is experienced by sexual and gender minorities not only in society, but also within the health care system (Alday-Mondaca & Lay-Lisboa, 2021; Ayhan et al, 2020). Health care providers including physicians (Prairie et al, 2018; Sabin et al, 2015), nurses (Englund et al, 2020; Grudzinski, 2019; Prairie et al, 2018; Stewart & O’Reilly, 2017), and mental health providers (Sabin et al, 2015) contribute to these discriminatory environments and experiences whether consciously or unconsciously.…”
Section: Introductionmentioning
confidence: 99%
“…These assumptions come into tension since a neutral perspective is not possible in relation to a moral judgment, which will inevitably be influenced by the sociocultural, political, and religious context in which discrimination against LGBTIQ+ people has been built, i.e. : heteronormativity [1,14,51,52].…”
Section: "Mejor Niñez" and The Adoption Processmentioning
confidence: 99%
“…In this process, there is a change in the law that follows most clearly in terms of clarity of processes, availability to the public, and coherence in the language used. At the moment there are obstacles in the symbolic, institutional, and factual spheres, which are related to the exercise of parenthood from sex-affective diversity, which can generate affective self-limitations associated with the (im)possibility of thinking of oneself as a potential mother/father [5,51].…”
Section: Registration Of Children In the Civil Registrymentioning
confidence: 99%
“…Studies of parenthood involving trans men have shown how challenging the parental experience -comprising assisted insemination, pregnancy, childbirth and parenting -can be 11,15 . The challenges listed were: discrimination and prejudice, exhaustive concern with protecting children from possible attacks [16][17][18][19][20] , difficulty in aligning gender performance and normative notions of paternity 6,21 , need for legal support 22 , absence of family emotional support and impaired mental health 19,23 . Another study also revealed vulnerability to depression and anxiety 24 due to stigma and violence.…”
Section: Introductionmentioning
confidence: 99%